The role of PLVAP in endothelial cells: review - Denzer, Lea; Muranyi, Walter; Schroten, Horst; Schwerk, Christian (Cell & tissue research)
Endothelial cells play a major part in the regulation of vascular permeability and angiogenesis. According to their duty to fit the needs of the underlying tissue, endothelial cells developed different subtypes with specific endothelial microdomains as caveolae, fenestrae and transendothelial channels which regulate nutrient exchange, leukocyte migration, and permeability. These microdomains can exhibit diaphragms that are formed by the endothelial cell-specific protein plasmalemma vesicle-associated protein (PLVAP), the only known protein component of these diaphragms. Several studies displayed an involvement of PLVAP in diseases as cancer, traumatic spinal cord injury, acute ischemic brain disease, transplant glomerulopathy, Norrie disease and diabetic retinopathy. Besides an upregulation of PLVAP expression within these diseases, pro-angiogenic or pro-inflammatory responses were observed. On the other hand, loss of PLVAP in knockout mice leads to premature mortality due to disrupted homeostasis. Generally, PLVAP is considered as a major factor influencing the permeability of endothelial cells and, finally, to be involved in the regulation of vascular permeability. Following these observations, PLVAP is debated as a novel therapeutic target with respect to the different vascular beds and tissues. In this review, we highlight the structure and functions of PLVAP in different endothelial types in health and disease.
Online veröffentlicht: 13. Februar 2023
Gesehen am 15.02.2024